2007
DOI: 10.1002/hep.1840020509
|View full text |Cite
|
Sign up to set email alerts
|

Histologic Observations in Human Hepatitis Non-A, Non-B

Abstract: Specimens from 57 patients with acute or chronic hepatitis non-A, non-B (HNANB), mostly mild to moderate, were studied by light and, in 22 instances, by electron microscopy. They were compared to specimens of hepatitis A and hepatitis B on file or obtained simultaneously with the HNANB cases. In the HNANB material, two types of light-microscopic lesions were noted in the lobular parenchyma singly or in combination. One was an eosinophilic alteration of the hepatocytic cytoplasm associated with many acidophilic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 169 publications
(22 citation statements)
references
References 31 publications
1
18
0
3
Order By: Relevance
“…If all these factors of fatty liver are excluded, the prevalence of steatosis in chronic hepatitis C is still approximately 40%—that is, about a twofold increase compared with chronic hepatitis B 66 67. This suggests that HCV may directly cause fatty liver, at least in a subgroup of patients with chronic hepatitis C. Indeed, the association is so strong that in the pre-serology era it was used as a diagnostic tool to identify patients with chronic non-A, non-B hepatitis 68 69…”
Section: Hcv and Fatty Livermentioning
confidence: 99%
“…If all these factors of fatty liver are excluded, the prevalence of steatosis in chronic hepatitis C is still approximately 40%—that is, about a twofold increase compared with chronic hepatitis B 66 67. This suggests that HCV may directly cause fatty liver, at least in a subgroup of patients with chronic hepatitis C. Indeed, the association is so strong that in the pre-serology era it was used as a diagnostic tool to identify patients with chronic non-A, non-B hepatitis 68 69…”
Section: Hcv and Fatty Livermentioning
confidence: 99%
“…26 The increase of serum lactate dehydrogenase in severe acute pancreatitis suggests latent liver damage and was reported to correlate with mortality. 27 Hepatocyte apoptosis has been observed in various disease conditions, such as viral or chemical hepatitis, 28 allograft rejection, 29 portal vein ligation, 30 and ischemic-reperfusion injury. 31 In particular, Bohlinger et al 11 reported that hepatocyte apoptosis was induced in mice with endotoxin shock.…”
Section: Apoptosis In Livermentioning
confidence: 99%
“…Most notably, the accumulation of neutral lipids in cytosolic lipid droplets in hepatocytes was defined as a pathologic hallmark of hepatitis C virus infection [8]. Early biophysical characterizations of virus particles in patient serum also revealed the virus to be highly heterogenous in buoyant density due to association with host lipoproteins [9,10].…”
Section: Introductionmentioning
confidence: 99%